Les dieux olympiens et la mer: espaces et pratiques cultuelles - Fenet, Annick (Collection de l'École française de Rome, 2016)
The sea represents a major geographical aspect of the ancient Greek world. It is hardly surprising that this element has permeated beliefs and cults, from the Atlantic to the Persian Gulf and especially to Greater Greece. This book explores the ways in which maritime culture has influenced the major figures of the Greek pantheon, the Olympian divinities, from Homer to the end of the Hellenistic period. All sources were required in such an investigation: literary, epigraphic, archaeological, iconographic, numismatic. By analyzing the beliefs, the topography of the sanctuaries, the practices of worship on board as well as the maritime ex-voto (anchors and boats), it is an indispensable tool for the study of the Greek religion as well as naval archeology